Determinants of Reading Difficulties Among Grade 7 Students at San Pascual National High School: Basis for an Intervention Program - Pascua, Moises (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the determinants of reading difficulties among Grade 7 students at San Pascual National High School as a basis for an intervention program. Anchored on Schema Theory, Vygotsky’s Social Development Theory, and the Simple View of Reading, the study explored how learner background and environment influence reading performance. A quantitative descriptive–correlational research design was employed involving 36 Grade 7 non-reader students selected through purposive sampling. Data were collected using a validated researcher-made questionnaire and analyzed using frequency, percentage, weighted mean, and Pearson r correlation. Findings revealed that learners generally demonstrated positive interest and motivation toward reading but exhibited limited prior knowledge and reading experiences. The school environment was found to be supportive, particularly through teacher guidance and availability of materials, while the home environment showed minimal support due to limited parental involvement and reading practices. Learners experienced significant difficulties in phonemic awareness, vocabulary knowledge, reading fluency, reading comprehension, and affective response, with vocabulary and comprehension identified as the most challenging areas. The study further revealed a strong and statistically significant relationship between learners’ background and reading difficulties (r = 0.68, p < 0.05) and between learners’ environment and reading difficulties (r = 0.76, p < 0.05). These findings indicate that both individual and contextual factors significantly influence reading performance. The study recommends targeted intervention programs focusing on reading skills development, enhancement of prior knowledge, and strengthened collaboration between schools and parents. This study aligns with SDG 4 (Quality Education) by addressing literacy challenges and improving learning outcomes, and SDG 10 (Reduced Inequalities) by highlighting socio-economic disparities in reading performance. It contributes to educational and socio-economic sustainability by supporting evidence-based literacy interventions and promoting inclusive learning environments.